A Dyadic Analysis of PTSD and Psychological Partner Aggression Among U.S. Iraq and Afghanistan Veterans: The Impact of Gender and Dual-Veteran Couple Status. Issue 5 (March 2021) - Watkins, Laura E.; Laws, Holly B.
Posttraumatic stress disorder (PTSD) symptoms have been repeatedly linked to intimate partner aggression (IPA), and previous research has suggested that this association may be stronger among veterans and men. However, few studies have examined veteran status and gender as moderators of the association between PTSD and psychological IPA, taking both partners' perspectives into account (i.e., within a dyadic framework). The current study aimed to address this limitation by using dyadic multilevel modeling to examine the association between PTSD symptoms and psychological IPA perpetration among a sample of 159 Operation Iraqi Freedom and Operation Enduring Freedom veterans and their partners ( N = 318 participants). Findings revealed that both one's own and one's partner's PTSD symptoms were positively associated with greater psychological IPA. In addition, the effects of partner PTSD symptoms on psychological IPA perpetration differed across gender and veteran status. Results suggested that the association of partner PTSD and IPA perpetration may be stronger for male veterans than for female veterans. Findings from the current study are consistent with previous research showing associations between PTSD and IPA, and have clinical implications for treatment of PTSD and IPA among Operation Iraqi Freedom and Operation Enduring Freedom veterans.